2006
DOI: 10.1097/01.rli.0000192421.81037.d5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Human Serum Albumin on Longitudinal and Transverse Relaxation Rates (R1 and R2) of Magnetic Resonance Contrast Agents

Abstract: Relaxation rates of Gd-BOPTA showed a strong dependency on HSA. In contrast, Gd-DTPA and Gd-BT-DO3A demonstrated little or no relevant dependency. On the basis of these results, the influence of serum protein concentration should be considered in both research studies and in clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
72
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(76 citation statements)
references
References 34 publications
3
72
0
1
Order By: Relevance
“…14,32,33 As a consequence, its R1 relaxivity in vivo is due entirely to the size and innate T1 shortening capacity of the gadobutrol molecule itself rather than to any augmentation of relaxivity and T1 shortening through interaction with serum albumin. Although reported relaxivity values vary slightly across publications depending on experimental conditions, 10,11,13 the results of well-conducted intraindividual comparative studies confirm that differences in relaxivity in vivo lead clinically to significantly better outcomes. 1,[5][6][7][8][34][35][36] A final consideration concerns the fact that this study was performed at 1.5T only.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…14,32,33 As a consequence, its R1 relaxivity in vivo is due entirely to the size and innate T1 shortening capacity of the gadobutrol molecule itself rather than to any augmentation of relaxivity and T1 shortening through interaction with serum albumin. Although reported relaxivity values vary slightly across publications depending on experimental conditions, 10,11,13 the results of well-conducted intraindividual comparative studies confirm that differences in relaxivity in vivo lead clinically to significantly better outcomes. 1,[5][6][7][8][34][35][36] A final consideration concerns the fact that this study was performed at 1.5T only.…”
Section: Discussionmentioning
confidence: 65%
“…[1][2][3][4][5][6][7][8] The superior diagnostic performance achievable with gadobenate dimeglumine, which is reflected in a recently updated "Summary of Product Characteristics," 9 is due to high in vivo R1 relaxivity (6.3-7.9 L ϫ mmol Ϫ1 ϫ sec Ϫ1 at 1.5T, 10,11 ) which derives from weak and transient interactions of the gadobenate contrast-effective molecule with serum albumin. 12,13 The increased R1 relaxivity leads to increased SI enhancement and thus significantly improved lesion visualization and better depiction of morphologic features relative to those achieved with GBCAs, which do not interact with serum protein, when these agents are administered at an equivalent dose of 0.1 mmol/kg of body weight. [1][2][3][4][5][6][7][8] Recently, gadobutrol (Gadavist [Gadovist]; Bayer Healthcare, Berlin, Germany) has been approved by the FDA for imaging of the CNS.…”
mentioning
confidence: 99%
“…Comparative studies in other indications have similarly highlighted the value of high-relaxivity gadobenate dimeglumine in permitting the use of lower doses. 21,22 As noted elsewhere, [23][24][25] the higher in vivo R1 relaxivity of gadobenate dimeglumine is due to weak, transient interaction of the gadobenate contrast- effective molecule with serum albumin, 26 which slows its molecular tumbling rate, leading to greater shortening of the T1 relaxation time and thus substantially increased signal intensity enhancement.…”
Section: Figmentioning
confidence: 99%
“…[1][2][3] Many of the included studies, however, used either a double dose of gadolinium contrast agent or a standard volume of [25][26][27][28][29][30] mL (corresponding to 0.17-0.2 mmol/kg for a 75-kg patient). Although some studies have used lower doses, this use has often been associated with compromised spatial resolution and image quality.…”
mentioning
confidence: 99%
“…[6][7][8] Because of weak and transient protein binding, this agent has been reported to possess enhanced (R1 and R2) relaxivities and, therefore, faster transverse and longitudinal relaxation and recovery rates compared with the other FDA-approved GBMCAs. [7][8][9][10] In clinical trials, it has been found to confer greater conspicuity and detectability to lesions within the central nervous system and associated cerebral vasculature, among other reported benefits. [11][12][13][14][15][16] However, even in the intraindividual crossover studies, biodistribution of contrast within each patient, therefore the local concentration of contrast, cannot be determined or controlled.…”
mentioning
confidence: 99%